Work as Art: Links between Creative Work and Human Development - Kabanda, Patrick (United Nations Development Programme, 2016)
Creative work has enhanced human development since early times; similarly, the latter can expand the former. But the links are not automatic. Creative work can be rife with exploitation and gender bias. Writers can advance human welfare, yet illiterate people may not benefit. To expand the contribution of creative work to human development, this paper suggests cultivating more respect for local creative output, fighting exploitation and gender bias, promoting intellectual property, and collecting data and building infrastructure.
Keywords: Arts Education, Creative Work, Creativity, Cultural Diversity, Cultural Policy, Gender Bias, Home Bias, Human Development, Innovation, Intellectual Property, Local Knowledge, Public Goods, Social Utility